Immersive, Creative, Inclusive: Areas of cross-fertilization between accessible captions for D/deaf audiences for the stage and for the screen - Mevel, Pierre-Alexis; Robinson, Jo; Tennent, Paul (Journal of Audiovisual Translation, 2022)
In a deliberate and valiant effort to adapt to the conditions created by the recent pandemic, many theatre companies across the globe shifted their activities from the stage to online video platforms. But in releasing large portions of their back-catalogues at speed, opportunities to make such shows accessible have been under-exploited. This migration has created an unprecedented opportunity to examine the way accessible practices are transferred from stage to screen and has brought into sharp focus the somewhat inadequate provision for accessibility of online video platforms. While the very practice of making these shows available online, often at no cost to the viewer, has made them more socially accessible, practical accessibility for portions of the audience, such as the D/deaf community, has often been ignored or addressed in a low fidelity way. Through lack of time, lack of expertise or lack of resources, many companies have resorted to the use of auto-captioning tools, or the most basic of captions. Rarely do such captions come close to capturing the creativity of the shows they represent. This paper represents a call to arms for the development of bespoke tools to support better, more immersive and creative, retroactive captioning of stage productions presented as videos. Lay Summary In this article, we discuss how videos of stage performances can be subtitled in a way that is accurate and that preserves the creativity original performances. The recent pandemic forced theatre companies to adapt or perish. With playhouses closed, some companies moved their activities online. They either released old footage of their past shows and performances on video platforms such as YouTube but did not necessarily have the time or the right tools to make these videos accessible to members of the D/deaf community. One the one hand, their shows are more easily accessed since they can be found online, but on the other hand, whole sections of the general public, such as D/deaf people, still cannot accessed these videos because they are not subtitled. Most video platforms have built-in tools that can generate subtitles automatically, but these are not very precise and do not help to convey the creativity of the performances. The tools that are currently available are therefore not suitable and new tools need to be developed to provide access to D/deaf people and do justice to the performances.